Quase-verdade e pragmatismo - Vercesi, Roque Pires [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This work is inserted in the context of the Philosophy of Logic and in the topic theories of truth. Reflections of theories of truth put in evidence questions of interest in the philosophical, scientific and logical environment: "What is the truth?". This tradition is very long, with reflections that go back to antiquity and are still very relevant in the academic world, as can be seen by the recent litera-ture about this issue. Aristotle was a precursor of this search by proposing that the truth could be characterized according to their maximum: "To say of what is that it is not, or of what is not that it is, is false, while to say of what is that it is, and of what is not that it is not, is true”. Posteriorly, this question of the truth was carefully treated by many authors who have developed theories and/or principles to de-termine what is true or what makes something true (criteria of truth). Among the theories of truth usually discussed, we find the theories: correspondence, co-herence, pragmatic, redundancy and semantic conception of Tarski. We dedicate an initial chapter to these theories of truth, when we list their essential characteristics. Recently, the theory of quasi-truth has gained importance in the reflections about the truth, which has as a precursor Profes-sor Newton da Costa, Brazilian exponent in the context of Logic. In 1986, Mikenberg, Costa and Chuaqui introduced the theory of quasi-truth in the arti-cle Pragmatic truth and approximation to truth, published in "The Journal of Symbolic Logic". A second goal of this Dissertation is the understanding of this concep-tion of true, the quasi-truth, and their respective formalism. As the theoretical development of quasi-truth was motivated by the semantic conception of Tar-ski, which is understood as one of many theories about quasi-truth, then be-fore our development on the quasi-truth, we will present a chapter about truth, according to Alfred Tarski. Next, we presented our understanding about the quasi-truth. We visited the original texts and others who brought new contributions to the quasi-truth, as the quasi-satisfaction of Bueno and Souza (1996). We also discussed about the recent version developed by Silvestrini (2011) that brings innovations on the formalization of quasi-truth. In the next chapter, we present another philosophical relevant concep-tion to this thesis, the pragmatism. As described in the title of the first article of quasi-truth of 1986: "Pragmatic truth and approach to the truth," the quasi-truth was linked with aspects of pragmatism. Pragmatism is a very broad philosophical theme and for this reason, we will discuss just a part of this theory in the text. Even the version of the prag-matic conception of truth is quite extensive. Thereby, we consider a presenta-tion of three pioneers of pragmatism: Charles Pierce, William James and John Dewey. We emphasize the aspects that highlight their views about the theory of truth. In the final chapter, we will analyze how much exist of the pragmatism in the quasi-truth theory, which we sought to understand during the thesis devel-opment.

Este trabalho está inserido no contexto da Filosofia da Lógica e no tópi-co teorias da verdade. As reflexões das teorias da verdade colocam em evi-dência a seguinte questão de interesse no ambiente filosófico, científico e ló-gico: “O que é a verdade?”. Esta tradição é bem longa, com reflexões que remontam à Antiguidade e ainda hoje são bastante pertinentes no mundo acadêmico, como podemos observar pela recente literatura sobre o assunto. Aristóteles foi um precursor desta busca ao propor que a verdade pode-ria ser caracterizada segundo sua máxima: “Dizer do que é, que ele não é, ou do que não é, que ele é, é falso; enquanto dizer do que é, que ele é, ou do que não é, que ele não é, é verdadeiro”. Posteriormente, essa questão referente à verdade foi minuciosamente tratada por muitos autores, que elaboraram teorias e/ou buscaram princípios para determinar o que é verdade ou o que torna algo verdadeiro (critério de verdade). Entre as teorias da verdade usualmente discu-tidas encontramos as teorias correspondencial, coerencial, pragmática, da re-dundância e a concepção semântica de Tarski. Dedicaremos um capítulo inicial a estas teorias da verdade, quando elencamos as suas características essenciais. Recentemente, a teoria da qua-se verdade tem conquistado importância nas reflexões sobre a verdade, que tem como um precursor o professor Newton da Costa, expoente brasileiro no âmbito da Lógica. Em 1986, Mikenberg, da Costa e Chuaqui introduziram a teoria da quase verdade no artigo Pragmatic truth and approximation to truth, publicado no “The Journal of Symbolic Logic”. Uma segunda meta desta Dissertação é o entendimento desta concep-ção de verdade, a quase verdade, e seu respectivo formalismo. Como este de-senvolvimento teórico da quase-verdade foi motivada pela concepção semân-tica de Tarski, a qual é entendida como uma das muitas teorias da quase ver-dade, então antes do nosso desenvolvimento sobre a quase-verdade, faremos um capítulo sobre a verdade segundo Alfred Tarski. A seguir, apresentamos o nosso entendimento da quase-verdade. Revi-sitamos os textos iniciais e outros que trouxeram novas contribuições para a quase-verdade, como a quase-satisfação de Bueno e de Souza de 1996. Tam-bém tratamos da recente versão de Silvestrini, de 2011, que traz inovações so-bre a formalização da quase-verdade. No Capítulo seguinte, apresentamos outra concepção filosófica relevan-te para esta Dissertação, o pragmatismo. Como está no título do artigo inicial da quase-verdade de 1986: “Verdade pragmática e aproximação à verdade”, a quase-verdade foi vinculada com aspectos do pragmatismo. O pragmatismo é um tema filosófico muito amplo e, certamente, não da-ríamos conta de retratá-lo no texto. Mesmo a versão da concepção pragmática da verdade é bastante extensa. Assim, consideraremos uma apresentação de três pioneiros do pragmatismo: Charles Pierce, Willian James e John Dewey. Procuramos destacar aspectos que destacam suas visões sobre a teoria da verdade. No capítulo final, faremos uma análise de quanto há de pragmatismo na teria da quase-verdade que buscamos entender no desenvolvimento desta Dissertação.
Quasi-truth and pragmatism
Keywords: Theories of truth; Quasi-truth; Quasi-satisfaction; Carriers of truth; Pragmatic truth; Teorias da verdade; Quase-verdade; Quase-satisfação; Portadores de verdade; Verdade pragmática